2000
DOI: 10.1097/00002030-200003100-00006
|View full text |Cite
|
Sign up to set email alerts
|

Plasma RNA viral load predicts the rate of CD4 T cell decline and death in HIV-2-infected patients in West Africa

Abstract: This longitudinal study shows for the first time that a baseline HIV-2 RNA load predicts the rate of disease progression. HIV-2-infected patients with a high viral load may need to be treated as vigorously as HIV-1 patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 37 publications
4
34
0
Order By: Relevance
“…Two longitudinal studies of patients living in West Africa reported a link between HIV-2 viral load and the CD4 cell count decline and death (2,11). In the French Agence Nationale de Recherche sur le SIDA HIV-2 cohort study, we confirmed the very slow progression of HIV-2 disease and showed that, as in HIV-1 infection, plasma RNA quantification was predictive of the risk of clinical progression (14).…”
supporting
confidence: 58%
“…Two longitudinal studies of patients living in West Africa reported a link between HIV-2 viral load and the CD4 cell count decline and death (2,11). In the French Agence Nationale de Recherche sur le SIDA HIV-2 cohort study, we confirmed the very slow progression of HIV-2 disease and showed that, as in HIV-1 infection, plasma RNA quantification was predictive of the risk of clinical progression (14).…”
supporting
confidence: 58%
“…Of these, three studies identified evidence of KSHV-DNA in peripheral blood cells (Chang et al, 1996;Kasolo et al, 1997;Belec et al, 1998), two used a lytic antibody assay alone (He et al, 1998;Lampinen et al, 2000), five used a latent antibody assay alone Ariyoshi et al, 1998;Bestetti et al, 1998;Bourboulia et al, 1998;Sitas et al, 1999) and 18 used both a lytic and a latent assay (Lennette et al, 1996;Simpson et al, 1996;Mayama et al, 1998;Olsen et al, 1988;Ablashi et al, 1999;Andreoni et al, 1999Andreoni et al, , 2002Enbom et al, 1999;Gessain et al, 1999;Wilkinson et al, 1999;Engels et al, 2000;Rezza et al, 2000;Gaye Serraino-Diallo et al, 2001;Kakoola et al, 2001;Nuvor et al, 2001;Serraino et al, 2001;Wawer et al, 2001). The results are presented in Table 1, together with the estimated cumulative incidence of Kaposi's sarcoma in men aged 0 -64 years in the period before HIV infection (Cook-Mozaffari et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Weakly positive HIV-1 or HIV-2 tests or dually positive results were tested by a synthetic peptide-based strip method (Peptilav 1-2; Sanofi Diagnostics Pasteur). Indeterminate results were subjected to HIV-1- and HIV-2-specific PCR using nested primers based on long terminal repeat (LTR) regions specific for the respective virus (7,47). Patients with confirmed HIV-1/HIV-2 dual status were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the majority of HIV-2-infected individuals are asymptomatic and die of causes unrelated to immunodeficiency (1). Although HIV-2 infection has no effect on survival in most adults, individuals who do progress to AIDS are clinically indistinguishable from those infected with HIV-1 (6,7), demonstrating that HIV-2 is not simply an attenuated virus.…”
Section: Introductionmentioning
confidence: 99%